Unicompartmental Knee Arthroplasty: Modes of Failure and Conversion to Total Knee Arthroplasty - Vasso, Michele (Joints, 2017)
Despite the excellent success rates of the modern unicompartmental knee arthroplasty (UKA), results of knee replacement registries still shows a relatively high revision and failure rate for UKA, especially when compared with traditional total knee arthroplasty (TKA). Bearing dislocation continues to be advocated as the predominant mechanism of failure in mobile UKA, whereas polyethylene wear and aseptic loosening remains the main cause of failure of fixed UKA. Degeneration of the unreplaced compartments has been reported in both mobile and fixed designs. When the revision is required, most of failed UKAs are converted to TKAs. Surgical challenges of the UKA revision, and outcomes of UKA converted to TKA are still debated in literature.